Bonnier novels I (1976–77) - Språkbanken Text (University of Gothenburg, 2024)
A corpus of 69 Bonnier novels from 1976–77

En korpus med 69 Bonniersromaner från 1976–77
Bonniersromaner I (1976–77)
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik